PELAKSANAAN KATEKESE PERSIAPAN PERKAWINAN DI PAROKI ST. YOSEP PASSO KEUSKUPAN AMBOINA - Fautngilyanan, Maria Gema; Refo, Ignasius SS. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2017)
The Catholic Church considers that marriage is a covenant between men and women that from between the whole life togetherness. This is why, in the Catholic view, the marriage is one and cannot be divorced. Therefore, the Catholic Church always doing preparation for those who will be solemnized their marriage. This article is an effort to explain catechesis of marriage preparation in St. Joseph’ Parish in the Diocese of Amboina. Usingqualitative methods, it is suspected to find accurate data on the implementation of catechetical marriage preparation in St. Joseph’ Paris.